Cowardly Clyde - Peet, Bill. (Boston : Houghton Mifflin, 1979)
For a war horse, Clyde is an abysmal coward, but he finally decides that even if he isn't brave he can at least act brave for his knight, Sir Galavant.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
3.2
K-3
Keywords: Courage -- Fiction; Horses -- Fiction; Horses -- Fiction; Courage -- Fiction